Tensile Performance of High Ductility Cementitious Composites With Recycled Powder From C&D Waste - Ji, Jing; Song, Huayu; Jiang, Liangqin; Ren, Hongguo; Zhang, Yunfeng; Liu, Yingchun (Frontiers in Materials, 2021)
The effects of recycled powder (RP) on hydration, micro-structures, compressive strength and tensile properties of high-ductility cementitious composites (HDCC) were studied. Three mass ratios of RP ranging from 10, 30 to 60% were employed to partially replace the cement. The hydration kinetics of RP-amended matrix was measured to investigate the influence of RP on the cementitious hydration process and the phase development was quantified by the thermal gravimetric analysis. Mechanical properties, including the compressive and tensile properties of HDCCs were obtained at 28 days. The morphology of reinforced polyethylene fiber at the fracture surface was obtained by the environmental scanning electron microscope (SEM) analysis.